PEMBERDAYAAN UMKM MELALUI PRODUKSI KRIPIK KULIT AYAM DAN KRIPIK TEMPE SEBAGAI ALTERNATIF USAHA RUMAHAN DI KELURAHAN RENON - Widiastuti, Ni Putu; Farhaeni, Mutria; Prastyandhari, I Gusti Ayu Ika Monika; Martini, Luh Kadek Budi (Jurnal Abdi Insani, 2025)
Renon Village is located in the South Denpasar District, Denpasar City, Bali. Renon Village has a fairly extensive livestock sector with significant potential for business development, both in the livestock sector and in the livestock sector. One of the livestock products found in Renon Village is skin crackers. The purpose of this community service project was to empower Micro, Small, and Medium Enterprises (MSMEs) and the community in Renon Village, Denpasar, through the development of chicken skin chips and tempeh chips production businesses as alternative home-based businesses. The background to this activity was the high potential of local raw materials that had not been optimally utilized, as well as the community's need for business opportunities that could improve family finances. The implementation methods included socialization, training in raw material processing, production process mentoring, and the handover and use of production equipment. The results of the activity showed an increase in participants' skills in processing raw materials into marketable products, the emergence of entrepreneurial motivation, and an increase in knowledge related to business management and simple marketing strategies. Through this activity, the community is expected to be able to independently develop chicken skin chips and tempeh chips businesses, thereby enhancing the competitiveness of local SMEs and driving economic growth in Renon Village, Denpasar.